2013
DOI: 10.5799/ahinjs.01.2013.03.0287
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between subclinical hypothyroidism and serum homocysteine concentration in premenopausal women

Abstract: Objective: In our study we aimed to examine serum homocysteinelevels of patients without thyroid dysfunctionswho have high serum anti thyroid peroxidase (anti-TPO)levels and patients with subclinical hypothyroidism whohave high serum thyroid stimulating hormone (TSH) andanti-TPO levels.Methods: One hundred and seven premenopause femaleoutpatients who referred to endocrine clinic of our hospitalwere included in our study. We generated 3 groups. Firstgroup (Control) consists of 53 (50%) patients between theages … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2016
2016
2016
2016

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 18 publications
0
1
0
Order By: Relevance
“…Homocysteine is one of the popular risk factors in this topic. In epidemiological studies, it was shown that hyper-homocysteinemia is an independent risk factor for coronary heart disease, peripheral vascular disorder and stroke and that an independent predictor for cardiovascular mortality in atherosclerotic patients [12][13][14][15][16][17][18].…”
Section: Introductionmentioning
confidence: 99%
“…Homocysteine is one of the popular risk factors in this topic. In epidemiological studies, it was shown that hyper-homocysteinemia is an independent risk factor for coronary heart disease, peripheral vascular disorder and stroke and that an independent predictor for cardiovascular mortality in atherosclerotic patients [12][13][14][15][16][17][18].…”
Section: Introductionmentioning
confidence: 99%